Temperature-compensated bioimpedance system for estimating body composition. - Ji-Jer Huang
The influence of temperature variation on segmental fat-free mass estimation is considered. A bioelectrical impedance measurement system with temperature compensation is proposed for estimation of segmental body composition. A segmental conductor model of the human body is also proposed, consisting of eight conductors. The system is also designed with a user-friendly graphic interface for ease of measurement.
Keywords: Bioelectrical impedance measurement system; Human body; Medical instrumentation; Segmental conductor model; Segmental fat-free mass estimation; Temperature-compensated bioimpedance system; User-friendly graphic interface